Dussel no caleidoscópio da filosofia contemporânea: origem, originalidade e problemas da filosofia da libertação - Oliveira, Hudson Mandotti de (2012)
The present dissertational study proposes to analyze the present problems in the Philosophy of Liberation by Enrique Dussel, from essential questions: variations of the constitutive dusselian structure of thinking as to the origin and originality; the problem of passage from liberty to liberation, which Dussel s definitions remain in an open process and elaborative; the pretension of an ethical argumentative counterhegemonic which translates as the utopianism of a macro-ethical and their hermeneutical issues, and the maturation of dusselian thinking from the architectonic of politics of liberation. These different angles imply the relationship between subject-other, thus referring to the aspect of responsibility essentially ethical. To understand this study, it is necessary to decipher the different perspectives that the philosopher himself will travel, thus demonstrating a constructa formed by four distinctive axis, namely - the problem of being that occurs in Heidegger's Dasein and the purpose of the unveiling of the existential experience; the historical question and the hermeneutics of itself in Ricoeur; the problem of subjectivity and the transcendence in Levinas; and the political-economic questions in the reading of historical and dialectical materialism of Marx - whose only intention is the liberation of the victim